AUTOMATIC CODE GENERATION IN GROUP TECHNOLOGY (International Journal of Engineering Sciences & Management Research, 2018)
In this paper, we present a new method of part grouping based on actual demand of the user requirements or needs. A new algorithm is used to classify the parts into different groups using dynamic method. Here we try to match non parametric values and exactly identify the difference from old parts with new orders. Finally codes can be generated based on the manufacturer requirements